Implementasi Program Majelis Taklim Nisaiyah dalam Meningkatkan Kualitas Akhlak para Anggota Majelis Taklim di Pusdai Jawa Barat - Fadhila Altarans; Chairiawaty; Asep Ahmad Siddiq (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. Nisaiyah taklim assembly program to improve the moral quality of taklim assembly members in Pusdai West Java. This aims to deepen the knowledge of Islamic religion as a means of religious teaching and a means of da'wah. The research object is the Nisaiyah taklim assembly using qualitative research. Data collection techniques through observation, interviews and documentation. The research results show that one of the Islamic religious education institutions is organized in non-formal education so that it has the aim of increasing istiqomah, devotion and faith in Allah SWT. Abstrak. Program majelis taklim nisaiyah dalam meningkatkan kualitas akhlak para anggota majelis taklim di Pusdai Jawa Barat. Ini bertujuan untuk memperdalam lagi tentang ilmu agama Islam sebagai sarana pengajaran agama dan sarana dakwah. Obyek penelitian yaitu majelis taklim nisaiyah menggunakan penelitian kualitatif. Teknik pengumpulan data melalui observasi,wawancara,dan dokumentasi. Hasil penelitian menunjukan salah satu lembaga pendidikan keagamaan Islam yang diselenggarakan dalam pendidikan nonformal sehingga mempunya tujuan untuk meningkatkan istiqomah, ketaqwaan dan keimanan kepada Allah SWT.